The Effect of Profitability in Improving Sustainability Performance with Good Corporate Governance as a Moderating Variable: A Study on Mining Companies - Astiana Masayu Asmara; Januar Eko Prasetio (AIBPM Publisher, 2024)
The objective of this study is whether profitability affects sustainability performance with Good Corporate Governance (GCG) as a moderating variable in energy sector mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023. GCG in this study is proxied by the number of board directors' meetings and the number of audit committee meetings. By using a purposive sampling technique, for the period 2020-2023, the research data amounted to 37. The data analysis technique used in descriptive statistical analysis, classical assumption test, linear regression analysis, and Moderated Regression Analysis (MRA). The results of this study indicate that profitability has no effect on sustainability performance in energy sector mining companies listed on the IDX, while GCG is able to moderate or strengthen the relationship between profitability on sustainability performance. This research provides insight for companies and stakeholders to pay attention to the role of GCG in improving corporate sustainability.